Rac-GEF/Rac Signaling and Metastatic Dissemination in Lung Cancer - Cooke, Mariana; Baker, Martin J.; Kazanietz, Marcelo G. (Frontiers in Cell and Developmental Biology, 2020)
Lung cancer is the leading cause of cancer-related deaths worldwide, with non-small cell lung cancer (NSCLC) representing ~85% of new diagnoses. The disease is often detected in an advanced metastatic stage, with poor prognosis and clinical outcome. In order to escape from the primary tumor, cancer cells acquire highly motile and invasive phenotypes that involve the dynamic reorganization of the actin cytoskeleton. These processes are tightly regulated by Rac1, a small G-protein that participates in the formation of actin-rich membrane protrusions required for cancer cell motility and for the secretion of extracellular matrix (ECM)-degrading proteases. In this perspective article we focus on the mechanisms leading to aberrant Rac1 signaling in NSCLC progression and metastasis, highlighting the role of Rac Guanine nucleotide Exchange Factors (GEFs). A plausible scenario is that specific Rac-GEFs activate discrete intracellular pools of Rac1, leading to unique functional responses in the context of specific oncogenic drivers, such as mutant EGFR or mutant KRAS. The identification of dysregulated Rac signaling regulators may serve to predict critical biomarkers for metastatic disease in lung cancer patients, ultimately aiding in refining patient prognosis and decision-making in the clinical setting.